Biomimetic Spider-web like Electrospun Nanofbrous Membrane of Nylon-6 for Future Air Filtration - Pant, Hem Raj (Journal of the Institute of Engineering, 2016)
In this work, methoxy poly(ethylene glycol) (MPEG) oligomer with viscous supporting nylon-6 solution was fabricated in the form of natural spider-web like structure via an electrospinning process. Field-emission scanning electron microscopy (FE-SEM) showed that this network consists of thinner MPEG nanofbers, approximately 15 ± 5 nm in diameter connected with thicker nylon-6 main nanofbers, arranged in spider-web like structure. TGA and XRD analysis showed that the hybrid mat of MPEG and nylon-6 was formed during electrospinning. These two different interconnected nanofbers were separated by extraction of MPEG from the fbrous mat in cold water and identifed. The molecular weight and purity of the extracted MPEG was determined by gel permeation chromatography (GPC) and Fourier transform infrared (FT-IR) analysis, respectively. The decreased average pore diameter and increased hydrophilicity of the hybrid mat, caused by spider-web like structure, can make it as a potential candidate for air fltration. Journal of the Institute of Engineering, 2015, 11(1): 108-115